Meta-analysis of predictive models to assess the clinical validity and utility for patient-centered medical decision making: application to the CAncer of the Prostate Risk Assessment (CAPRA) - Lorent, Marine; Maalmi, Haifa; Tessier, Philippe; Supiot, Stéphane; Dantan, Etienne; Foucher, Yohann (BMC medical informatics and decision making, 2019)
The Cancer of the Prostate Risk Assessment (CAPRA) score was designed and validated several times to predict the biochemical recurrence-free survival after a radical prostatectomy. Our objectives were, first, to study the clinical validity of the CAPRA score, and, second, to assess its clinical utility for stratified medicine from an original patient-centered approach.